Tinjauan Yuridis terhadap Mekanisme Penyelidikan pada Tindak Pidana Penipuan Melalui Media Transaksi Elektronik oleh Kepolisian dalam Sistem Peradilan Pidana di Indonesia - Trisutrisno Chandra; Akhmad Munawar; Muhammad Aini (CV Rewang Rencang, 2024)
Fraud through electronic transaction media is one of the crimes that is growing rapidly in the digital era. Advances in information technology provide opportunities for perpetrators to utilize digital platforms such as e-commerce and social media to carry out various modes of fraud. This research aims to analyze the investigation mechanism carried out by the police regarding this criminal act in the criminal justice system in Indonesia. Using normative legal research methods, this research examines relevant laws and regulations, such as the Criminal Procedure Code and the ITE Law, as well as the obstacles faced in carrying out investigations, such as technological limitations, apparatus competence, and difficulties in tracking the perpetrator's digital footprints. The research results show that although regulations have provided a legal basis for cracking down on electronic transaction fraud, there are technical and administrative obstacles that hamper the effectiveness of law enforcement. To overcome this, regulatory updates are needed, strengthening the capacity of law enforcement officers, and increasing public digital literacy. In conclusion, the success of investigative mechanisms depends greatly on the synergy between adaptive regulations, adequate technology, and effective cross-institutional cooperation to create justice for victims and a sense of security in online transactions.